Adoptive Transfer of Glypican-3 Peptide-Specific Cd8 T Lymphocytes Causes Regression of Testicular Yolk Sac Tumor in Mice - He, Guorong; Congde Chen, Haochuan Zhang; Xiaoming Chen, Xin-He Lai Yi Ren (International Journal of Innovative Research in Medical Science, 2016)
Background: Glypican-3 (GPC3) is overexpressed in testicular yolk sac tumor (TYST) which has a poor prognosis and needs novel effective treatment strategies. The potential of GPC3 as a cancer vaccine for TYST was explored in mice in the current study. Methods: Mice were vaccinated with GPC3144-152, CD8+ T cells were purified from isolated splenocytes and adoptively transferred to mice with TYST tumor xenograft. Tumor growth was monitored by measuring its volume change; tumors were examined for their cellular GPC3 expression, CD8 T cell infiltration, and cell death by immunohistochemistry and TUNEL staining, respectively. Results: Splenocytes from mice vaccinated with GPC3144-152 was able to produce IFN-γ. Adoptive transfer of enriched mouse CD8 T lymphocytes from the splenocytes of these immune mice to the nude mice with xenograft TYST tumor resulted in CD8 T cell infiltration, apoptosis induction and inhibition of GPC3 expression in the tumor tissue, and ultimately caused the regression of the xenograft TYST tumor in a CD8 T cell dependent manner without inducing autoimmunity. Conclusions: To the best of our knowledge, this study is the first demonstrating that adoptive transfer of GPC3 peptide-specific CD8 T cells conferred mice with TYST tumor xenograft the capability to inhibit GPC3 expression and tumor growth. Thus, GPC3 peptide vaccination could be a useful supplementary treatment for TYST.